▼Ulipristal – a new emergency contraceptive pill. Issue 8 (4th August 2010) - Unknown
Abstract : Until recently, women in the UK who wanted emergency contraception had two options: an oral hormonal method (levonorgestrel), which is licensed for use up to 3 days after unprotected sexual intercourse; or a copper-bearing intrauterine device (IUD), which can be inserted up to 5 days after unprotected intercourse or up to 5 days after the earliest likely calculated ovulation. Now ▼ulipristal acetate (ellaOne – HRA Pharma), a new oral hormonal emergency contraceptive, has been licensed in the European Union for use within 120 hours (5 days) of unprotected intercourse.1 Here we assess whether it is an advance for emergency contraception.